Fiqih Sebagai Traffic-Light : Cermin Formulasi Fiqih ‘Umar Ibn Al-Khaththab - Duski Ibrahim (Medina-te : Jurnal Studi Islam, 2019)
This paper is entitled Fiqh as Traffic-Light: Mirror of Fiqh Formulation ‘Umar ibn al-Khaththab. The author wants to express the original fiqh that was advanced by the scholars and the majority of ‘Umar ibn al-Khaththab through the study of literature. This literature research study, therefore, uses qualitative data. The data is analyzed with relevant rules, especially Islamic maqshid rules. Based on studies and research conducted, the results are obtained that: First, fiqh is the result of human thought about Islamic law which is understood from the arguments of the Sunnah Al-Qur'an. Therefore, it can be used with a variety of considerations, making it suitable for every time and every place. Second, according to ‘Umar ibn al-Khathtab, the second Caliph, fiqh was the same as traffic light. Traffict-light work for traffic, while fiqh is done as a regulator of the journey of human life. The purpose of traffic-light is to realize the benefit of cross-country, while fiqh is to realize the benefit of human life. Therefore, if it cannot realize benefit, it can be shifted in a way that will bring benefit.